2022
DOI: 10.1177/00027642221142201
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Food Access in Flint: An Analysis of Racial and Socioeconomic Disparities

Abstract: The primary objective of this study was to describe the food landscape of Flint, Michigan, and the surrounding townships. We investigated the relationship between the location of food outlets and the racial composition of census tracts. We collected data from multiple sources; however, Data Axle, a repository of information on the U.S. and Canadian businesses, was our primary data source. Data were collected and verified between September 2020 and December 2021. The final fact-checking was completed in June 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(41 citation statements)
references
References 142 publications
0
23
0
Order By: Relevance
“…The city is often regarded as a food desert ( Sadler et al, 2013 ), and its food system has been described as dismantled. However, Taylor, Bell, et al (2022) argue that the food environment is more nuanced and robust than previously described. The researchers found that though access is not evenly distributed, Flint’s residents have access to traditional food outlets such as supermarkets and large grocery stores.…”
Section: Introductionmentioning
confidence: 88%
See 4 more Smart Citations
“…The city is often regarded as a food desert ( Sadler et al, 2013 ), and its food system has been described as dismantled. However, Taylor, Bell, et al (2022) argue that the food environment is more nuanced and robust than previously described. The researchers found that though access is not evenly distributed, Flint’s residents have access to traditional food outlets such as supermarkets and large grocery stores.…”
Section: Introductionmentioning
confidence: 88%
“…Our paper is a comprehensive study of the food landscape of Flint and surrounding townships that seeks to determine the extent of food outlet closures. We adopt a food systems approach explained in detail in Taylor, Bell, et al (2022) and Taylor and Ard (2015) . Hence, we consider not only traditional venues to obtain food, such as supermarkets, grocery stores, and restaurants, but alternative venues like farmers’ markets, community gardens, and emergency food outlets.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations